Exploring the Self Through Algorithmic Composition. - Alsop, Roger (Leonardo Music Journal, 1999)
The author discusses his views on musical composition in the late twentieth century, focusing on the influence that communication and computer technology have had over his pursuit. He goes on to describe his use of computer-based algorithmic composition and how this particular approach enhances and refines his understanding of his own musical self-expression. He describes four computer algorithms, used in recent compositions and improvisations, that reflect his particular musical interests.